A study of cerebrospinal fluid C-reactive protein in bacterial meningitis among paediatric age group in a tertiary care hospital - M., Unmesh Dev; Milind B. Kamble (International Journal of Contemporary Pediatrics, 2023)
Background: Bacterial meningitis is a significant cause of mortality and morbidity in children worldwide. C-reactive protein (CRP) raises rapidly in the first 24-48 hours of occurrence of bacterial meningitis and in large incremental increases thereafter. The present study was undertaken to find out the correlation between cerebrospinal fluid (CSF)-CRP and bacterial meningitis in paediatric age group. Methods: A total 123 children aged between 1 month to 12 years, in whom meningitis was suspected during the study period were included. Lumbar puncture performed at L3-L4 and CSF sample not more than 3 ml collected in 4 sterile containers. 1ml sent for protein and sugar, 0.5ml each sent for CSF cytology and CSF-CRP, 1ml sent for CSF culture sensitivity and gram staining. Results: The institutional incidence of bacterial meningitis was 3.37%. Fever (93.26%) and altered sensorium (92.30%), were the commonest symptoms and neck rigidity (58.65%) was the commonest meningeal sign. The neurologic assessment showed abnormal mental status (34.61%), abnormal cranial nerve findings (10.57%) and abnormal motor function (13.46%). The mean CRP level was 15.36±0.67 mg/l. Pneumococcus was the commonest isolated organism (53.48%) in CSF culture. The institutional mortality was 13.46%. CSF-CRP was positive in 104 (82.69%) of the culture-positive cases with a sensitivity of 82.69%, specificity 84.21%, positive predictive value 96.62% and negative predictive value of 47.05%. Conclusions: CRP levels in CSF offers a moderate sensitivity and specificity as well as high positive predictive value. This indicates that CSF-CRP is a better marker in differentiating bacterial meningitis and it can serve as a useful screening test for bacterial meningitis.